2021
DOI: 10.3390/cells10010182
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic 5′-Nucleotidase II Is a Sensor of Energy Charge and Oxidative Stress: A Possible Function as Metabolic Regulator

Abstract: Cytosolic 5′-nucleotidase II (NT5C2) is a highly regulated enzyme involved in the maintenance of intracellular purine and the pyrimidine compound pool. It dephosphorylates mainly IMP and GMP but is also active on AMP. This enzyme is highly expressed in tumors, and its activity correlates with a high rate of proliferation. In this paper, we show that the recombinant purified NT5C2, in the presence of a physiological concentration of the inhibitor inorganic phosphate, is very sensitive to changes in the adenylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…NT5C1, which has been mainly studied in skeletal muscle, and NT5C2, which is ubiquitously expressed, are the major cytosolic NT5Cs acting on intracellular nucleotides (Camici et al, 2020). Among purine nucleotides, AMP, with a K M in the millimolar range (Hunsucker et al, 2001;Tkacz-Stachowska et al, 2005) is the preferred substrate for NT5C1, while IMP and GMP are better substrates for NT5C2 (K M in the micromolar range) (Tozzi et al, 2013;Pesi et al, 2021), but this enzyme catalyzes also the hydrolysis of the phosphoester bond of AMP (with a K M in the millimolar range) (Tozzi et al, 2013). The intracellular concentrations of IMP, GMP and also AMP depend on the rate of the AMP-IMP-GMP cycles (Figure 2) which in turn depends on NT5C2 activity (Barsotti et al, 2003).…”
Section: '-Nucleotidasesmentioning
confidence: 99%
“…NT5C1, which has been mainly studied in skeletal muscle, and NT5C2, which is ubiquitously expressed, are the major cytosolic NT5Cs acting on intracellular nucleotides (Camici et al, 2020). Among purine nucleotides, AMP, with a K M in the millimolar range (Hunsucker et al, 2001;Tkacz-Stachowska et al, 2005) is the preferred substrate for NT5C1, while IMP and GMP are better substrates for NT5C2 (K M in the micromolar range) (Tozzi et al, 2013;Pesi et al, 2021), but this enzyme catalyzes also the hydrolysis of the phosphoester bond of AMP (with a K M in the millimolar range) (Tozzi et al, 2013). The intracellular concentrations of IMP, GMP and also AMP depend on the rate of the AMP-IMP-GMP cycles (Figure 2) which in turn depends on NT5C2 activity (Barsotti et al, 2003).…”
Section: '-Nucleotidasesmentioning
confidence: 99%
“…Structural analysis confirmed the existence of the two distinct conformations of cN-II obtained in the presence of allosteric effectors [7]. Oxidative stress causes the irreversible inactivation of the enzyme [8,9]. Therefore, K M and k cat of cN-II depend on the cell energy charge and on reactive oxygen species [8].…”
Section: Introductionmentioning
confidence: 54%
“…We have previously reported that, in several cell models, cN-II silencing is followed by an increase in oxidative metabolism and of antioxidant defenses [8,9,16]. Therefore, we measured reduced thiols in NCI-H292 cells and found that also in this cell model, they were slightly more abundant in pScNII cells and the incubation with pifithrin-α was able to reduce their level both in pScont and pScNII cells (Figure 4A).…”
Section: Cn-ii Silencing Increases Oxidative Metabolism and Thiol Content In Nci-h292 Cellsmentioning
confidence: 62%
See 2 more Smart Citations